Field Survey of Flank Collapse and Run-up Heights due to 2018 Anak Krakatau Tsunami - Esteban, Miguel; Takabatake, Tomoyuki; Achiari, Hendra; Mikami, Takahito; Nakamura, Ryota; Gelfi, Mustarakh; Panalaran, Satriyo; Nishida, Yuta; Inagaki, Naoto; Chadwick, Christopher; et al. (Journal of Coastal and Hydraulic Structures, 2021)
On the 22nd of December 2018 tsunami waves generated by the flank collapse of the Anak Krakatau volcano in Indonesia flooded the shorelines of the nearby Sumatra and Java islands. The authors conducted a field survey of the Krakatau group of islands to clarify the volume of the collapsed flank and the run-up of the tsunami around the island themselves. To aid with the simulation of this complex tsunami and document the current situation of the islands, bathymetric surveys, aerial drone and panoramic video mapping were also carried out. The results show that while much of the source directionality was towards the SE of Anak Krakatau, significant wave run-ups were also measured towards the NW, indicating that further numerical modelling is needed to fully explain this event.